Interactive Multimedia Utilizing Adobe Flash for Elementary School Students’ Fine Art - Desi Kristiyawati; Deasylina da Ary (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2024)
Interactive media is needed to help teachers so that learning can run optimally. This study aims to develop,  evaluate the feasibility, and measure the effectiveness of interactive multimedia based on Adobe Flash in improving student learning outcomes in fine arts lessons on plastic waste craft materials. This study follows the Borg and Gall research model. The participants consisted of 20 fourth-grade students. Data collection methods include test techniques by conducting pretest and post-test assessments as well as non-test techniques in the form of observation, questionnaires, and interviews. The results of the study namely Adobe Flash Media was considered good by experts and was deemed suitable for use as a learning medium. The effectiveness of this media is shown by an increase in the average pretest and post-test score of 30.85 and the t-test results show a significance of < 0.05 with an n-gain of 0.7043 which is included in the high category. This media received a positive response from teachers and students. This media has proven to be effective, practical, and suitable for use to improve learning outcomes in the fine arts subject of plastic waste craft materials for grade IV of SDN 1 Trembulrejo.